2015
DOI: 10.1038/bmt.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

Preserved in vivo reconstitution ability of PBSCs cryopreserved for a decade at −80 °C

Abstract: PBSC products for auto-and allografting can be cryopreserved in liquid nitrogen with controlled-rate freezing until their use. Alternatively, they can be stored at − 80°C in a mechanical chest freezer, but it remains to be clarified whether PBSCs can be stored for the long term. We evaluated viability and functions of PBSCs cryopreserved for more than 10 years with this simplified method. Although recovery rate and viability of CD34 + cells were significantly decreased, myeloid differentiation potential and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Marrow is usually cryopreserved in 10% DMSO, and studies have shown that marrow, as well as peripheral blood stem cells and umbilical cord blood, may remain cryopreserved for a long period of time (>10 years) while retaining stem cell/progenitor activities for use in clinical practice. [12][13][14] Shen and colleagues demonstrated that marrow preserved for 23 to 25 years was effective for MSC culture production with adequate growth characteristics and adequate amounts of adherent, healthy MSCs. 15 Those authors investigated old frozen marrow specimens as starting material (n 5 20) for MSCs, but the controls (n 5 20) were not paired from the same donors.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow is usually cryopreserved in 10% DMSO, and studies have shown that marrow, as well as peripheral blood stem cells and umbilical cord blood, may remain cryopreserved for a long period of time (>10 years) while retaining stem cell/progenitor activities for use in clinical practice. [12][13][14] Shen and colleagues demonstrated that marrow preserved for 23 to 25 years was effective for MSC culture production with adequate growth characteristics and adequate amounts of adherent, healthy MSCs. 15 Those authors investigated old frozen marrow specimens as starting material (n 5 20) for MSCs, but the controls (n 5 20) were not paired from the same donors.…”
Section: Discussionmentioning
confidence: 99%
“…To explore and validate easier and more cost-effective ways of cryopreservation of HSCs, freezing and storage of cells in a –80°C mechanical freezer has been examined. However, the recovery rate and viability of CD34+ cells were significantly decreased for PBSCs cryopreserved for 10 years with this method, although the myeloid differentiation potential, in vivo reconstitution, and self-renew potential of CD34+ cells were maintained [70]. Loss of CD34+ cells was even observed for HSCs cryopreserved by non-controlled rate freezing and stored at –80°C overnight [71].…”
Section: Additional Considerationsmentioning
confidence: 99%
“…To evaluate the quantity of CD34 + cell collection, aliquots (1.0 mL) of apheresis products were used. The frequencies of CD34 + cells were evaluated using BD Trucount Tubes (BD Biosciences) and FACSCant flow cytometry (BD Biosciences) as previously described 12 . The collected CD34 + cell counts were evaluated by multiplication of the CD34 + cells frequencies and total nucleated cell counts of apheresis products.…”
Section: Methodsmentioning
confidence: 99%